Pengaruh Arus Kas Operasi, Arus Kas Investasi dan Arus Kas Pendanaan terhadap PembayaranDeviden Tunai Pada PT. Semen Indonesia Tbk. (Periode 2011-2015) - Muhammad Ridha Ramli; Liya Aditia (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2017)
The purpose objectives for this kind of research are to analyzing and examining the influences of operation cash flow, investation cash flow and financing cash flow to dividen cash payment at PT. Semen Indonesia Tbk. During period 2011 -2015. After taking regression model we got the result of this research are : (1) operation cash flow, investation cash flow and financing cash flow stimultaneously have influences to dividen cash payment, (2) parttially operation cash flow has postive influences. But for investation cash flow and financing cash flow both are negatives influences